THE PÉ-DE-MEIA PROGRAM AS A PUBLIC POLICY TO ENCOURAGE STUDENTS TO STAY IN SCHOOL AND COMPLETE HIGH SCHOOL: EVIDENCE FROM THE FIRST RESULTS - Anízio, Jamilly de Lima Alcantara; da Silva, Josivan Anízio (Seven Editora, 2025)
Dropout and evasion in secondary education are historical challenges in Brazilian education, strongly associated with socioeconomic inequalities that compromise the permanence and completion of this stage by young people in the public school system. In this context, the Pé-de-Meia Program emerges as a public policy of financial incentive aimed at the permanence and completion of secondary education by vulnerable students in the public school system. This article aims to analyze initial evidence of the implementation of the Pé-de-Meia Program in light of selected indicators of school performance, flow, and transition, discussing the extent to which the policy design is compatible with improvements observed in the 2020-2024 period. Methodologically, this is a quantitative, descriptive, and ex post study based on secondary data from official databases (Inep, Nilo Peçanha Platform, and Enem statistics), with an emphasis on Figureical analysis and the comparison of historical series. The results point to signs of an association between the Program’s duration and higher pass rates, lower dropout and age-grade distortion indicators, and increased participation of public school graduates in the Enem, especially among students more exposed to the need for early entry into the labor market. It can be concluded that, although still preliminary and subject to important methodological limitations, the findings indicate the relevance of Pé-de-Meia as a policy to support high school retention and completion, highlighting the need for continued monitoring and more robust impact assessments as new data sets and series become available. DOI: https://doi.org/10.56238/sevened2025.036-148